1998
DOI: 10.1097/00005176-199808000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values of Body Composition Obtained by Dual Energy X-Ray Absorptiometry in Preterm and Term Neonates

Abstract: Normative data of dual-energy x-ray absorptiometry body composition for healthy preterm and term infants are provided and can therefore be used in research and in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
111
0
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(127 citation statements)
references
References 21 publications
9
111
0
7
Order By: Relevance
“…Females are shorter and weigh less than males at birth and throughout infancy but have more fat mass and less lean body mass than males, even in the neonatal period. [29][30][31] In 11-to 12-year olds the prevalence of overweight was higher in girls. 32,33 In Shantal children between 5 and 12 years old, fat patterning was different between girls and boys.…”
Section: Discussionmentioning
confidence: 98%
“…Females are shorter and weigh less than males at birth and throughout infancy but have more fat mass and less lean body mass than males, even in the neonatal period. [29][30][31] In 11-to 12-year olds the prevalence of overweight was higher in girls. 32,33 In Shantal children between 5 and 12 years old, fat patterning was different between girls and boys.…”
Section: Discussionmentioning
confidence: 98%
“…31 The only instrument that has been validated in studies that prove its precision and accuracy is total body DEXA, especially the fan beam 4500 A model by HOLOGIC, used in this study, according to the recommendations of other validation studies. 23,[32][33][34][35] One pertinent subject, the question of when is the best moment to initiate motor physical therapy, still requires an answer. A recent study showed that initiating a physical therapy protocol between the first and second weeks of life did not produce any improvement in bone mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Although the provision of bone-related nutrients at advised levels increases bone mineral accretion, ex utero bone mineral accretion rates do not equal in utero rates even with normal body weight gain. 4,5 Further, bone area (BA, cm 2 ) and mineral content (BMC, g) remain significantly lower than term infants at 1-year of age. 6,7 Older children and young adults who were born prematurely have significantly shorter stature with lower bone size and mineral content than their peers.…”
Section: Introductionmentioning
confidence: 92%